How Sweet It Is. Issue 1 (January 2015) - Taft, Natalie; Collier, David N.; Tanenberg, Robert J.; Kolasa, Kathryn M.
<x xml:space="preserve">Abstract</x> In this article, we present 4 cases from our medical practice to increase awareness of the role of sweet tea in obesity and diabetes management. We start with a history of Southern-style "sweet tea" and discuss the importance of screening for beverage intake in the clinical setting. We note the associations between sugar-sweetened beverage intake and weight that we often see in our clinics. Then we discuss resistance to changing a "sweet tea habit." Finally, we sound an alert about the spread of sweet tea to other parts of the country. The cases we present are not atypical for clinical populations.